2013
DOI: 10.1016/b978-0-444-63234-0.50142-1
|View full text |Cite
|
Sign up to set email alerts
|

Particle-Interaction Effects in Turbulent Channel Flow

Abstract: Large eddy simulation and a discrete element method are applied to study the flow, particle dispersion and agglomeration in a horizontal channel. The particle-particle interaction model is based on the Hertz-Mindlin approach with Johnson-KendallRoberts cohesion to allow the simulation of Van der Waals forces in a dry air flow. The influence of different particle surface energies on agglomeration, and the impact of fluid turbulence, are investigated. The agglomeration rate is found to be strongly influenced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The range in particle velocity fluctuations in the highest Re case demonstrates the significant influence of flow turbulence on particle agglomeration in both these regions. Relating the results of Figures 3 and 4, and the findings of Afkhami et al (2013), the difference in particle agglomeration between the various Reynolds numbers in the latter zones can be attributed to a combination of both the particle mean velocity and the particle velocity fluctuation. Finally, at the channel centre, the particle velocity fluctuation peak values are 0.6, 1.1 and 2.1 ms -1 , for Re = 150, 300 and 590.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The range in particle velocity fluctuations in the highest Re case demonstrates the significant influence of flow turbulence on particle agglomeration in both these regions. Relating the results of Figures 3 and 4, and the findings of Afkhami et al (2013), the difference in particle agglomeration between the various Reynolds numbers in the latter zones can be attributed to a combination of both the particle mean velocity and the particle velocity fluctuation. Finally, at the channel centre, the particle velocity fluctuation peak values are 0.6, 1.1 and 2.1 ms -1 , for Re = 150, 300 and 590.…”
Section: Resultsmentioning
confidence: 96%
“…For Re = 150, 300 and 590, at the channel centre (column 8) the number of bonds is 20, 18 and 47, respectively, with these values increasing towards the walls, where for columns 1 and 15 they increase to an average of 129, 203 and 249, respectively. Particle agglomeration near to the wall can be attributed to the high particle concentration and the high turbulence levels in this region (Afkhami et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best knowledge of the authors, no research has been reported on the effect of the inter-particle collisions on the particle behavior in horizontal duct turbulent flows or on the particle resuspension rate. However, similar studies by means of other geometries have been conducted such as the research of Yan et al [60] on particle dispersion in a turbulent jet, Afkhami et al [61] and Yamamoto et al [62] in a channel.…”
Section: Motivation and Summary Of The Present Workmentioning
confidence: 86%